Bacterial community diversity and its potential contributions to the flavor components of traditional smoked horsemeat sausage in Xinjiang, China - Jiang, Lei; Chen, Yu; Deng, Li; Liu, Fei; Wang, Tengbin; Shi, Xuewei; Wang, Bin (Frontiers in Microbiology, 2022)
Smoked horsemeat sausage is a famous fermented traditional food in Xinjiang, China. However, the microbial diversity and its potential contributions to the flavour components of smoked horsemeat sausage are unclear. In this study, the microbial community and flavour components of smoked horsemeat sausage from six regions of Xinjiang were measured by using amplicon sequencing and headspace solid-phase microextraction combined with gas chromatography–mass spectrometry (HS-SPME-GC–MS) technology, respectively. Relations among microbial communities, flavour components and environmental factors were subsequently predicted based on redundancy analysis (RDA) and Monte Carlo permutation tests. Although smoked horsemeat sausage samples from different regions possessed distinct microbial communities, lactic acid bacteria (LAB) were identified as the dominant consortium in smoked horsemeat sausage. Lactobacillus, Vagococcus, Lactococcus and Carnobacterium were detected at high abundance in different sausages. The moisture content, nitrite content and pH of the sausage might be important factors influencing the dominant bacterial community, according to the RDA. Among the dominant consortia, the eight core bacterial genera showed considerable correlations with the formation of sixteen volatile compounds in smoked horsemeat sausage based on multivariate statistical analysis. For example, the levels of Leuconostoc and Lactobacillus were positively correlated with those of 1-hexadecanol, hexyl acetate, 2-methyl-phenol, 1-pentanol, d-limonene and 2-heptanone, and the levels of Leuconostoc, Lactobacillus and Weissella were negatively correlated with those of 1-octanol, acetic acid, octanal, heptanal and 1-hexanol. This study will provide a theoretical basis for understanding the microbial metabolic modes of Xinjiang smoked horsemeat sausages.